Guideline-Concordant Antiviral Treatment in Children at High Risk for Influenza Complications. (22nd July 2022) - Antoon, James W; Hall, Matt; Feinstein, James A; Kyler, Kathryn E; Shah, Samir S; Girdwood, Sonya Tang; Goldman, Jennifer L; Grijalva, Carlos G; Williams, Derek J
Abstract: Background: National guidelines recommend antiviral treatment for children with influenza at high risk for complications regardless of symptom duration. Little is known about concordance of clinical practice with this recommendation. Methods: We performed a cross-sectional study of outpatient children (aged 1–18 years) at high risk for complications who were diagnosed with influenza during the 2016–2019 influenza seasons. High-risk status was determined using an existing definition that includes age, comorbidities, and residence in a long-term care facility. The primary outcome was influenza antiviral dispensing within 2 days of influenza diagnosis. We determined patient- and provider-level factors associated with guideline-concordant treatment using multivariable logistic regression. Results: Of the 274 213 children with influenza at high risk for influenza complications, 159 350 (58.1%) received antiviral treatment. Antiviral treatment was associated with the presence of asthma (aOR, 1.13; 95% confidence interval [CI], 1.11–1.16), immunosuppression (aOR, 1.10; 95% CI, 1.05–1.16), complex chronic conditions (aOR, 1.04; 95% CI, 1.01–1.07), and index encounter in the urgent care setting (aOR, 1.3; 95% CI, 1.26–1.34). Factors associated with decreased odds of antiviral treatment include age 2–5 years compared with 6–17 years (aOR, 0.95; 95% CI, .93–.97), residing in a chronic care facility (aOR, .61; 95% CI, .46–.81), and index encounter in an emergency department (aOR, 0.66; 95% CI, .63–.71). Conclusions: Among children with influenza at high risk for complications, 42% did not receive guideline-concordant antiviral treatment. Further study is needed to elucidate barriers to appropriate use of antivirals in this vulnerable population. Abstract : Among children with influenza at high risk for complications, 42% did not receive guideline-concordant antiviral treatment. Antiviral treatment varied according to a number of patient- and provider-level factors. Further study is needed to elucidate barriers to appropriate use of antivirals in children.